The Role of Environmental Conditions on Master Marathon Running Performance in 1,280,557 Finishers the ‘New York City Marathon’ From 1970 to 2019 - Knechtle, Beat; McGrath, Carlyn; Goncerz, Olivia; Villiger, Elias; Nikolaidis, Pantelis Theodoros; Marcin, Thimo; Sousa, Caio Victor (Frontiers in Physiology, 2021)
Aim: This study investigated the influence of weather conditions on running performance in female and male age group runners in the largest marathon in the world, the ‘New York City Marathon’. Methods: The analysis included data from 1,280,557 finishers the 'New York City Marathon' from the years 1970 to 2019. Linear mixed models for men and women finishers with race time (min) as dependent variable and 5-year age groups, temperature, wind and relative humidity tertiles (low, medium, high) as independent factors and finisher as random intercept was performed. Additional models with an interaction between age groups and one weather variable each were performed. Results: Temperature was positively associated with race time while windspeed and humidity were negatively associated (p<0.001). Men were significantly greater affected windspeed and humidity than women (p<0.001 for interaction) but not by temperature (p=0.17 for interaction). With an average of 8 min longer race time, high temperature had the greatest effect on race time. The effect of high humidity on race time was significantly increased in 40-59 years old men and 25-65 years old women. High temperatures had an increased effect on race time in 30-64 years old men and 40-64 years old women. The inverse association between race time and high windspeed was pronounced in finishers with younger age. Conclusion: Performance was lower on days with high temperature, low humidity and low windspeed. Men seemed to benefit more from higher humidity and windspeed than women. Aged (70+) finishers were not greater affected by high temperatures.